Morphological characterization, molecular identification, and phylogenetic analysis of Lasiodiplodia theobromae associated with CCN-51 cacao plants in Ecuador (Scientia Agropecuaria, 2025)
Necrotrophic fungi are pathogens that cause tissue death in plants, which negatively impacts their growth and productivity. This study focused on identifying the presence of Lasiodiplodia theobromae in CCN-51 cacao plants in the Simón Bolívar canton in Ecuador. We sampled cacao pods exhibiting necrotic lesions and obtained fungal isolates for morphological and molecular characterization. Techniques, such as culturing on selective media, microscopy, and DNA sequencing were used to confirm the fungal identity. We compared our results with international databases and assessed the genetic variability of the isolates. Morphological characterization placed the fungal isolates within the family Botryosphaeriaceae, and molecular analysis using ITS and EF1-α regions confirmed the species as Lasiodiplodia theobromae, with 100% DNA quality for amplicon analysis and 100% sequence similarity in GenBank. We constructed phylogenetic trees using maximum likelihood methods, which revealed high genetic similarity and recent divergence among sequences despite their varied geographic origins. The fungal isolates specifically confirmed the presence of L. theobromae as the causal agent of necrotic lesions in CCN-51 cacao pods from Simón Bolívar. These findings underscore the importance of studying necrotrophic fungi in cacao plants to inform control strategies, improve crop resistance, and support sustainable production, essential to the global cacao trade.